The ontology, origin, and impact of divisive public sector rules: A meta-narrative review of the red tape and administrative burden literatures - Campbell, J.W., Pandey, S.K. and Arnesen, L. (Public Administration Review)
A rule is divisive when its legitimacy is contested and divisive rules are an enduring theme of public administration research. For over three decades, this research has been shaped by red tape theory, which conceptualizes divisive rules as those which consume an organization's resources but fail to advance its goals. Recently, however, the administrative burden framework, which prioritizes the impact of divisive rules on citizens and links their origins to political motives, has grown in popularity. We take stock of the last decade of research on red tape and administrative burden using the meta-narrative review methodology. We identify five narratives within the two research traditions and discuss their distinct research questions, theoretical mechanisms, privileged actors, and rule assumptions, as well as their strengths, limitations, and practical implications. These insights are leveraged to analyze the origins, impact, and ontology of divisive public sector rules. We also raise research questions with cross-cutting relevance to the red tape and administrative burden research traditions.- Reproduced